What does a person's eating identity add to environmental influences on fruit and vegetable intake?. (1st January 2018) - Ma, Xiaonan; Blake, Christine E.; Barnes, Timothy L.; Bell, Bethany A.; Liese, Angela D.
Abstract: Objective: To evaluate whether knowledge of a person's eating identity (EI) can explain any additional variation in fruit and vegetable intake above and beyond that explained by food environment characteristics, perceptions of the food environment, and shopping behaviors. Design: Cross-sectional study. Setting: A total of 968 adults were recruited for a telephone survey by the Survey Research Laboratory in an eight-county region in South Carolina. Subjects: The survey queried information on shopping behaviors, perceptions of the food environment, demographic and address information, fruit and vegetable intake, and EI. EI was assessed using the Eating Identity Type Inventory, a 12-item instrument that differentiates four eating identity types: healthy, emotional, meat, and picky. Statistical analyses were restricted to 819 participants with complete data. Results: Healthy EI and picky EI were significantly and directly related to fruit and vegetable intake, with coefficients of 0.31 (p-value<0.001) for healthy EI and −0.16 (p-value<0.001) for picky EI, whereas emotional EI (β = 0.00, p-value = 0.905) and meat EI (β = −0.04, p-value = 0.258) showed no association. Shopping frequency also directly and significantly influenced fruit and vegetable intake (β = 0.13, p-value = 0.033). With the inclusion of EI, 16.3% of the variation in fruit and vegetable intake was explained. Conclusions: Perceptions and GIS-based measures of environmental factors alone do not explain a substantial amount of variation in fruit and vegetable intake. EI, especially healthy EI and picky EI, is an important, independent predictor of fruit and vegetable intake and contributes significantly to explaining the variation in fruit and vegetable intake.